Crescimento e produtividade de camomila e supressão de plantas daninhas em diferentes manejos - Puhl, Andressa Janaína (2019)
Growth of chamomile culture and its productivity of chamomile and essential oil can be affected by infesting communities of weed. Thus, the usage of different spacings between plants and sowing dates could provide an alternative for controlling, since one of the greatest problems faced by producers is weed infestation along the cycle. This work aimed to evaluate the weed community through phytosociological analysis, growth, productivity and chamomile essential oil under competition against weeds in different sowing dates and spacings between plants, in its beginning as well as in full flourishing. The experiment took place in Santa Maria – RS with four sowing dates in the year 2017 (18/03, 28/04, 30/06 and 31/08) and seven spacings along plants in lines (0,05, 0,10, 0,15, 0,20, 0,25, 0,30 and 0,40 m), spaced 0,30 m in between each other, as well as two sowing dates in 2018 (28/03 and 14/05) with four spacings along plants in lines (0,05, 0,10, 0,15 and 0,20 m) and two types of weed management (fully hoed and hoed once.) The evaluated phytosociological parameters were frequency (F), abundance (A), density (D), relative frequency (FR), relative abundance (AR) and relative density (DR). The growth variables analyzed were dry mass of leaves (MSF), reproductive structures (MSER), total aerial part (MSPA), leaf area (AF), leaf area index (IAF), as well as dry mass of chamomile and weeds by m- ². Productivity of dry floral chapters, content and productivity of essential oil were also evaluated. 17 species of weed were identified, distributed among 10 families. The Asteraceae family presented the largest number of specimens. In sowings from fall 2017 the Asteraceae specimen were the most frequent, and in 2017 winter sowings were the Poaceae. In 2018, specimens of Plantagynaceae and Polygonaceae families obtained the highest values in the analyzed parameters. The species with highest occurrence in the fall were Galinsoga parviflora Cav. and Soliva anthemifolia (Juss.) Sweet in 2017, and Galinsoga parviflora Cav., Rumex obtusifolius L as well as Veronica persica Poir in 2018. In the winter 2017, Richardia brasiliensis G., Amaranthus deflexus L. and Urochloa plantaginea (Link) R. D. Webster. For chamomile growth variables and dry mass of weeds, there was interaction between sowing dates and spacing between plants for MSF, AF and IAF in full chamomile flourishing. For the MSPA and MSER variables as well as dry mass of weeds, the effect of factors was isolated for the sowing dates of 2017 and 2018. The lowest dry mass of weeds and highest IAF of chamomile plants were obtained in the 0,05 m spacing. Individual chamomile plants grew more in the largest spacings tested. The productivity of dry floral chapters was greater in sowings from the fall of both years. In 2018, the highest productivity of essential oil was obtained in the sowing of March and the content of essential oil in the sowing of May.